2018
DOI: 10.5694/mja17.01164
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated care for patients with cirrhosis: fewer liver‐related emergency admissions and improved survival

Abstract: Objectives: To compare the incidence of liver‐related emergency admissions and survival of patients after hospitalisation for decompensated cirrhosis at two major hospitals, one applying a coordinated chronic disease management model (U1), the other standard care (U2); to examine predictors of mortality for these patients. Design: Retrospective observational cohort study. Setting: Two major tertiary hospitals in an Australian capital city. Participants: Patients admitted with a diagnosis of decompensated cirrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Hepatic cirrhosis and lung infections were the other most relevant diagnostic risk factors. Admissions for hepatic cirrhosis generally occur in terminal stages of the disease (RAMACHANDRAN et al, 2018). Respiratory infections, however, are amongst the top reasons for hospital admissions in Brazil (GOMES et al, 2010), many times as complications of other major underlying disease (BAHLIS et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic cirrhosis and lung infections were the other most relevant diagnostic risk factors. Admissions for hepatic cirrhosis generally occur in terminal stages of the disease (RAMACHANDRAN et al, 2018). Respiratory infections, however, are amongst the top reasons for hospital admissions in Brazil (GOMES et al, 2010), many times as complications of other major underlying disease (BAHLIS et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(7,(89)(90)(91)(92)(93)(94) Most involved implementation of new multidisciplinary "chronic disease management" models or "patient care management" programs to improve postdischarge care and prevent readmission. Three studies delivered face-to-face interventions (89,92,93) and two studies used modern technologies (90,91) to assist with remote management of medications and liver disease complications. While outcome measures varied, most studies reported reduced readmission rates (including for potentially medication-preventable complications, like ascites and HE) but not medication-specific outcome measures, like adherence or MRPs.…”
Section: Patient-oriented Interventionmentioning
confidence: 99%
“…(99,100) Given the degree of frailty that is commonly present in people Wigg et al (89) Single-center prospective, randomized, controlled, parallel-group study design; al. (93) Retrospective observational cohort study between two tertiary hospitals (unit 1 vs. unit 2);…”
Section: Patient-oriented Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the MJA , Ramachandran and colleagues 10 report the results of a retrospective study in which they compared the rates of liver‐related emergency admissions and survival for patients hospitalised for decompensated cirrhosis at two major metropolitan hospitals, one of which had implemented chronic disease management for patients with liver disease. This comprehensive liver failure program was a nurse‐led model of care with support from specialist hepatologists.…”
mentioning
confidence: 99%